The relationship between knowledge level and compliance to blood supplement tablets consumption in adolescent girls - Salhaj, Siti Rufiah; Sumiati, Sumiati; Anam, Khoirul; Meihartati, Tuti (Science Midwifery, 2024)
Anemia is one of the top 3 burdens of malnutrition in Southeast Asia. Globally, iron deficiency anemia is the leading cause of morbidity and mortality among adolescent girls aged 10-19 years. during the last 3 years the consumption coverage rate was only 44%. TTD Knowledge is one of the factors that can influence a person's TTD consumption behavior, because knowledge is the dominant factor in shaping a person's actions. To determine the relationship between knowledge level and compliance of TTD consumption among adolescent girls at SMPN 4 Tanjung Redeb, Berau Regency. This study used analytic descriptive quantitative research methods with a cross sectional research approach. With a total sample size of 76 people. Based on the results of the Spearman rank correlation test, the p value is 0.020, where this figure is <0.05, which means Ha is accepted and Ho is rejected, so it can be concluded that there is a relationship between knowledge and compliance of adolescents girls of SMPN 4 Tanjung Redeb in taking blood supplement tablets, There is a relationship between knowledge and compliance in adolescent girls in the consumption of TTD in adolescent girls.